FILSAFAT EKONOMI ADAM SMITH - Wijaya, Cuk Ananta (Jurnal Filsafat "WISDOM", 2009)
AbstractThis essay wants to describe and analyze Adam Smithâs philosophy of Economic. Adam Smith, as the Father of Economics,has really attempted to make economics as a positive-empiricalscience. The science starts and finishes in empirical datas andeliminates theological and speculative explanations. Realityâ ultimate reality, is the appearance or empirical reality.Keyword: philosophy of Economic, Adam Smith, a positiveempiricalscience, empirical reality.